1994
DOI: 10.1103/physreva.49.449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of finite bandwidth on the resonance fluorescence spectrum inside of a cavity

Abstract: We have considered the steady-state resonance fluorescence spectrum for a beam of two-level atoms, interacting with a strong driving field with a finite bandwidth inside a cavity. The competitive effects of cavity losses and the finite bandwidth of the intense driving laser beam on the resonance fluorescence spectrum have been discussed. Our results show that the usual three-peaked resonance fluorescence spectrum starts merging back into the central peak as the bandwidth of the driving field increases. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, ordinary lasers have definite linewidths. Here, we first discuss the effect of the laser linewidth [56][57][58][59] for the present scheme. The Rabi frequencies l (l = 1, 2, 3) have fluctuating phases ψ l (t) (l = 1, 2, 3), which are characterized by the random force d dt ψ l (t) = f l (t) with zero averages and white noise correlations…”
Section: Discussionmentioning
confidence: 99%
“…However, ordinary lasers have definite linewidths. Here, we first discuss the effect of the laser linewidth [56][57][58][59] for the present scheme. The Rabi frequencies l (l = 1, 2, 3) have fluctuating phases ψ l (t) (l = 1, 2, 3), which are characterized by the random force d dt ψ l (t) = f l (t) with zero averages and white noise correlations…”
Section: Discussionmentioning
confidence: 99%
“…Another typical example of a stochastic perturbation of a system of coherently driven two-level atoms is the phase noise of the laser field. The effect of the linewidth of the driving laser on the spectrum has been widely investigated in the literature [29,30,31,32,33], but no quantum interference effects have been found. In reference [34], however, it is suggested that an interference phenomenon similar to that induced by collisional noise can appear due to a large phase noise of the driving laser field.…”
Section: Introductionmentioning
confidence: 99%